2019
DOI: 10.5812/ijcm.88750
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Gland Involvement and the Efficiency of Thyroidectomy in Patients Having Larynx and Hypopharyngeal Cancers Treated with Surgery

Abstract: Background: Thyroid gland involvement and invasion during larynx and hypopharynx cancers is rare, but due to the anatomical closeness of the thyroid gland and the larynx, it could occur through local invasion. Thyroidectomy is usually performed in patients with thyroid gland involvement having larynx and hypopharyngeal cancers. A lot of controversies exist regarding the thyroid gland involvement and efficiency of a different kind of thyroidectomy intraoperatively in these types of cancers. Objectives: Thus, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…An additional nine articles were found from reference review. After full‐text review of the 105 candidate records, 51 studies 1–4,7,8,12–14,20,24–64 were included in the review. A summary of study characteristics can be found in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…An additional nine articles were found from reference review. After full‐text review of the 105 candidate records, 51 studies 1–4,7,8,12–14,20,24–64 were included in the review. A summary of study characteristics can be found in Table S1.…”
Section: Resultsmentioning
confidence: 99%